Suspected brodifacoum poisoning in tuatara (Sphenodon punctatus) - Mehta S; Booth L; Hunter S; Jolly M; Gartrell BD (Taylor and Francis Group on behalf of the New Zealand Veterinary Association, 2025)
Case history: Between June 2017 and April 2019, three captive tuatara from a zoological facility in the South Island of New Zealand were found unwell and admitted to veterinary care. One other tuatara from the same facility was found dead from misadventure in May 2019. Clinical findings: All three unwell tuatara showed clinical signs of lethargy, mucous membrane pallor, and dehydration, with haematoma formation/swelling in dependent parts of the body. Fine needle aspiration and cytology of the swellings showed common features of peripheral blood, with variable other cytological findings. Haematology confirmed marked anaemia in Case 1 (PCV 5%; reference range 22–53%) and Case 2 (PCV 1%) and suspected mild anaemia in Case 3 (PCV 27%). Case 1 died 6 weeks after initial presentation, whereas Cases 2 and 3 died soon after presentation. Pathological findings: Post-mortem examination showed general pallor of soft tissues in the three tuatara with clinical signs of coagulopathy. There was haemorrhage in the bladder wall of Case 1, while Cases 2 and 3 had haematomas (subcutaneous in Case 2 and peri-oesophageal in Case 3). The pathological diagnosis in Case 4 was death by asphyxiation following burrow collapse. Retrospective analysis showed brodifacoum was present in liver tissue at a concentration of 0.26 mg/kg in Case 3, and in skeletal muscle tissue at concentrations of 0.019 mg/kg in Case 2 and 0.035 mg/kg in the non-clinical case (Case 4). Diagnosis: The clinical signs and post-mortem findings were consistent with anticoagulant poisoning in three tuatara, and tissue concentrations of brodifacoum demonstrated exposure in three animals, including one animal with no clinical signs of coagulopathy (Case 4). Definitive diagnosis was prevented, however, by inconsistent toxicology testing and a limited understanding of toxicity thresholds in reptiles in general, and tuatara specifically. Clinical relevance: This case series suggests that tuatara are susceptible to anticoagulant poisoning and this has implications for both the captive management of tuatara, and also the use of rodenticides in tuatara habitat, such as offshore islands and mainland sanctuaries.
Keywords: Anticoagulant; coagulopathy; reptile; Sphenodontidae; tuatara; wildlife pathology